Lymphangiogenesis and angiogenesis in abdominal aortic aneurysm. - Masaki Sano; Takeshi Sasaki; Satoshi Hirakawa; Junichi Sakabe; Mikako Ogawa; Satoshi Baba; Nobuhiro Zaima; Hiroki Tanaka; Kazunori Inuzuka; Naoto Yamamoto; Mitsutoshi Setou; Kohji Sato; et al. (PLoS ONE, 2014)
The pathogenesis of abdominal aortic aneurysm (AAA) is characterized to be inflammation-associated degeneration of vascular wall. Neovascularization is regularly found in human AAA and considered to play critical roles in the development and rupture of AAA. However, little is known about lymphangiogenesis in AAA. The purpose of this study was to demonstrate both angiogenesis and lymphangiogenesis in AAA. Abdominal aortic tissue was harvested either from autopsy (control group) and during open-repair surgery for AAA (AAA group). Adventitial lymphatic vasa vasorum was observed in both groups, but seemed to be no significant morphological changes in AAA. Immunohistochemical studies identified infiltration of lymphatic vessel endothelial hyaluronan receptor (LYVE) -1, vascular endothelial growth factor (VEGF)-C, and matrix metalloproteinase (MMP)-9-positive macrophages and podoplanin and Prox-1-positive microvessels in the intima/media in AAA wall, where hypoxia-inducible factors (HIF)-1α was expressed. VEGF-C and MMP-9 were not expressed in macrophages infiltrating in the adventitia. Intraoperative indocyanine green fluorescence lymphography revealed lymph stasis in intima/medial in AAA. Fluorescence microscopy of the collected samples also confirmed the accumulation of lymph in the intima/media but not in adventitia. These results demonstrate that infiltration of macrophages in intima/media is associated with lymphangiogenesis and angiogenesis in AAA. Lymph-drainage appeared to be insufficient in the AAA wall.